La problématique de la santé communautaire dans les espaces périphériques de Port-Au-Prince (Haïti) dans le contexte socio-politique actuel : entre enjeux et défis - James Fleurilus (Études Caribéennes)
This research is based on the issue of community health in Haiti, particularly in peripheral areas of the Port-Au-Prince metropolitan area. It is the result of fieldwork carried out with twenty (20) multi-purpose community health workers (ASCP) working in communes in the Port-Au-Prince metropolitan area. This research presents part of the complexity of the tasks performed by multi-purpose community health workers, and also enables us to grasp the practical meaning of community health as a strategy for social action and appropriate health intervention in a given social space. The results of this research show us the level of complexity that crowns the exercise of their tasks. This study does not pretend to know everything about the complexity of their work. Using a qualitative method based on semi-directive interviews, this research aims to identify the complexity of the work of ASCPs in a difficult socio-political context in Haiti. In this perspective, this work gives us a contextualized reading of the problematic of the exercise of the function of ASCP in Haiti in their mission of prevention, education and health promotion while inscribing their work in a logic of social action, social accompaniment and in a perspective of work psychodynamics.